‎“TOPOGRAPHY OF THE THYROID GLAND, ITS BLOOD SUPPLY AND HISTOLOGICAL STRUCTURE IN ONE ‎HUMPED CAMEL” (CAMELUS DROMEDERIUS).‎ - J . Y . D. Al-Fayaz; N. S. Al-Samarrae; K. A.H. Al-‎ Nuaini‎ (The Iraqi Journal of Veterinary Medicine, 2024)
The thyroid gland of Camelus dromedrius is located directly behind the larynx. It consists of two lateral lobes at the sides of trachea. The lobes are connected to each other by a caudal isthmus from the ventral surface. The lobes extend to the seventh tracheal ring and even to the eighth or ninth ring. The medial surface of the lobes is adhered to trachea. The lateral surfaces are convex. Also, the dorsal and ventral edges of the lobes are convex.